HAp@GO drug delivery vehicle with dual‐stimuli‐triggered drug release property and efficient synergistic therapy function against cancer. Issue 10 (13th June 2019) - Sang, Rui; Chen, Min; Yang, Yuanyi; Li, Yunfei; Shi, Jiacheng; Deng, Yi; Chen, Xianchun; Yang, Weizhong
Abstract: Nanoscale hydroxyapatite (HAp) is an optimal candidate material in biomedical area for its good biocompatibility and bioactivity. In this study, HAp nanorods are prepared via hydrothermal method and combined with monolayered graphene oxide (GO). The obtained HAp@GO with excellent biocompatibility is revealed to have high drug loading capacity (698.7 μg/mg) for anticancer drug doxorubicin (DOX) and efficient photothermal conversion property. And the drug release property of DOX loaded HAp@GO (HAp@GO‐DOX) is demonstrated to be controlled by pH and near‐infrared light, which is favorable for cancer therapy. in vitro studies on cancer therapy demonstrate that the combined treatment, compared with either chemotherapy or photothermal therapy alone, has better synergistic therapeutic effect. These findings prove the great potential application of the nanocomposites for cancer therapy.